"I Am Still With You": Dementia and the Christian Wayfarer. Issue 1 (2nd April 2016) - Kinghorn, Warren A.
Abstract : Persons with dementia suffer not only from neuropathology but also from cultural norms that exalt agency, privilege rationality, equate worth with capacity, and discourage disability and dependence. In Christian theological context, however, these are faulty assumptions that harm people with dementia. Christian tradition affirms, rather, that humans are integrated, whole-person, embodied souls on a journey to God; dependent on others and on God; and endowed by God with intrinsic worth that is unrelated to capacities. Four theological parameters—creation, participation, lament, and song—enable resistance to prevalent toxic social norms and promote faithful Christian re-membering of people with dementia.